ON THE QUESTION OF STUDYING BIBLE AND QURANIC PHRASEOLOGY IN UZBEK LINGUISTICS (American Journal of Interdisciplinary Research and Development, 2024)
The article is devoted to the analysis of the current state of the study of phraseology in Uzbekistan, in particular religious phraseological units based on the material of the Russian and Uzbek languages.